Extracellular Vesicle (EV) biohybrid systems for cancer therapy: Recent advances and future perspectives. (September 2021) - Ou, Yi-Hsuan; Liang, Jeremy; Czarny, Bertrand; Wacker, Matthias G.; Yu, Victor; Wang, Jiong-Wei; Pastorin, Giorgia
Abstract: Extracellular vesicles (EVs) are a class of cell-derived lipid-bilayer membrane vesicles secreted by almost all mammalian cells and involved in intercellular communication by shuttling various biological cargoes. Over the last decade, EVs – namely exosomes and microvesicles – have been extensively explored as next-generation nanoscale drug delivery systems (DDSs). This is in large due to their endogenous origin, which enables EVs to circumvent some of the limitations associated with existing cancer therapy approaches ( i.e. by preventing recognition by the immune system and improving selectivity towards tumor tissue). However, successful translation of these cell-derived vesicles into clinical applications has been hindered by several factors, among which the loading of exogenous therapeutic molecules still represents a great challenge. In order to address this issue and to further advance these biologically-derived systems as drug carriers, EV-biohybrid nano-DDSs, obtained through the fusion of EVs with conventional synthetic nano-DDSs, have recently been proposed as a valuable alternative as DDSs. Building on the idea of "combining the best of both worlds", a combination of these two unique entities aims to harness the beneficial properties associated with both EVs and conventional nano-DDSs, while overcoming the flaws of the individual components. These biohybrid systems also provide a unique opportunity for exploitation of new synergisms, often leading to improved therapeutic outcomes, thus paving the way for advancements in cancer therapy. This review aims to describe the recent developments of EV-biohybrid nano-DDSs in cancer therapy, to highlight the most promising results and breakthroughs, as well as to provide a glimpse on the possible intrinsic targeting mechanisms of EVs that can be bequeathed to their hybrid systems. Finally, we also provide some insights in the future perspectives of EV-hybrid DDSs.